Khan academy matemática no processo de ensino e aprendizagem: limites e possibilidades - Pinto, Juliano Caetano (2020)
This study focuses on Khan Academy Mathematics (KA), a digital platform, whose initial purpose is to enhance innovative teaching for elementary school students. The challenge of this study is to investigate how this design is established in schools that use this platform, highlighting the role of Specialized Computer Teachers who, through their management action, guarantee security and continuity to the platform in schools. In this sense, the challenging question can be presented thus: can the format in which KA is inserted in schools foster innovative learning or just enrich traditional teaching models? In order to seek the answer to this question, a general objective was proposed to the work: to analyze the potential of KA in promoting innovative teaching in the area of Mathematics. The specific ones unfold to verify, from the exploration of the literature, factors necessary for the application of KA in mathematics classes, as well as in the interrelation that occurs between teacher and student. The study, as part of a Professional Master's Program, proposes an intervention project that is embodied in models that can be used in the processes of continuing education for teachers or adopted by teachers when the first contacts with KA. The methodology of the work initially advocates the exploration of different authors who debate about KA, then searches and organizes the reflections raised by the contents of these literatures that allowed to criticize the platform, guided by a set of analytical categories as defined: 1 ) Teacher Training (FD); 2) Active Methodologies (MA); 3) Digital Information and Communication Technologies (TDIC); 4) Media; 5) Knowledge Society (SC) and Contexts of Uses. As results, pointed out by the indicated literature: the continuing education for teachers and the involvement of students in collaborative actions for the use of KA in schools. This unfolds in the recognition of the complexity of the educational action, demanding, therefore, the participation of all segments of the school - teachers, managers and employees - to experience innovative projects. The perspective of continuing this study would be to verify, in practice, before the schools that adopted KA, how the operation and its application took place, thus identifying the platform not only as a potential resource for teaching, but as a possibility for meaningful learning.